Advanced Java 1.1 programming - Rice, Jeffrey C. (McGraw-Hill Java masters, 1997)
Written by two Sun insiders intimately familiar with Java, this unique reference tool shows you how to develop full-featured GUIs in Java, write applets that interact directly with browsers, create reusable custom AWT widgets, implement multithreading applications, write code that interacts with CGI programs, use Java for client-server applications, introduce new protocols, create file access-control lists, and much more. Containing nearly 16,000 lines of printed source code (also on the accompanying CD-ROM, along with javadoc-generated HTML documentation, additional applets, and test programs), this timely reference emphasizes reusability. It also covers many of the more subtle, and useful, classes in Java's rich developer's kit. Full of real-world answers to the programming questions that software developers most frequently put to the expert authors, this book is chock full of the information you need today, tomorrow, and for many Java-filled years to come!